Implementation of Physical Fitness Test Measurement in Basketball Using an Application - Iqbal, Muhammad; Hartati, Hartati; Victorian, Ahmad Richard (Department of Physical Education, Sport, Health and Recreation, 2024)
This study focuses on the application of a fitness testing app to assess physical performance in junior high school students, specifically those involved in extracurricular basketball activities at Palembang 03 Public Junior High School. The primary objective is to establish norms for categorizing physical test results using the app, covering components such as speed, agility, strength, endurance, and muscle explosiveness. Employing a quantitative descriptive approach with survey research methods, the study involves 20 participants, comprising 10 male and 10 female students. Various physical tests, including a 30-meter run for speed, Bleep tests for agility, Push-Ups for strength, Bleep tests for endurance, and a vertical jump for muscle explosive power, were conducted as part of the data collection process. The research took place at Palembang 03 Public Junior High School in collaboration with the MGMP Pjok at the school. Analysis of the physical test results revealed that 9% of the participants achieved a